2021
DOI: 10.21203/rs.3.rs-726635/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regeneration of Collagen Fibrils at the Papillary Dermis by Reconstructing Basement Membrane at the Dermal-Epidermal Junction

Abstract: The epidermal basement membrane deteriorates with aging. We previously reported that basement membrane reconstruction not only serves to maintain epidermal stem/progenitor cells in the epidermis, but also increases collagen fibers in the papillary dermis. Here, we investigated the mechanism of the latter action. Collagen fibrils in the papillary dermis were increased in organotypic human skin culture treated with matrix metalloproteinase and heparinase inhibitors. The expression levels of COL5A1 and COL1A1 gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been postulated that disrupted basement membranes allow soluble melanogenic regulators from senescent fibroblasts to more easily stimulate melanocyte activity and accelerate age-related pigmentation (Goyarts et al, 2007;Amano, 2009;Iriyama et al, 2011b;Bastonini et al, 2016). Iriyama et al (2022) have shown that the inhibition of basement membrane degradation with MMP inhibitors and heparinase inhibitors promotes the deposition of laminin-511 at the DEJ, which in turn promotes the secretion of platelet-derived growth factor consisting of 2 B subunits (PDGF-BB). Expression of COL5A1 and COL1A1 genes was increased in the fibroblasts stimulated with PDGF-BB, suggesting increased collagen expression in the papillary dermis (Iriyama et al, 2022).…”
Section: Dermal Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that disrupted basement membranes allow soluble melanogenic regulators from senescent fibroblasts to more easily stimulate melanocyte activity and accelerate age-related pigmentation (Goyarts et al, 2007;Amano, 2009;Iriyama et al, 2011b;Bastonini et al, 2016). Iriyama et al (2022) have shown that the inhibition of basement membrane degradation with MMP inhibitors and heparinase inhibitors promotes the deposition of laminin-511 at the DEJ, which in turn promotes the secretion of platelet-derived growth factor consisting of 2 B subunits (PDGF-BB). Expression of COL5A1 and COL1A1 genes was increased in the fibroblasts stimulated with PDGF-BB, suggesting increased collagen expression in the papillary dermis (Iriyama et al, 2022).…”
Section: Dermal Agingmentioning
confidence: 99%
“…Iriyama et al (2022) have shown that the inhibition of basement membrane degradation with MMP inhibitors and heparinase inhibitors promotes the deposition of laminin-511 at the DEJ, which in turn promotes the secretion of platelet-derived growth factor consisting of 2 B subunits (PDGF-BB). Expression of COL5A1 and COL1A1 genes was increased in the fibroblasts stimulated with PDGF-BB, suggesting increased collagen expression in the papillary dermis (Iriyama et al, 2022). Therefore, strengthening the damaged basement membrane and restoring epidermaldermal integrity have been proposed as new anti-ageing targets, but the actual clinical significance of the DEJ and its role in aging requires much further research.…”
Section: Dermal Agingmentioning
confidence: 99%